Influência do consumo de farinha de yacon na glicemia, perfil lipídico, composição corporal e consumo alimentar com mulheres com diabetes tipo 2 e com excesso de peso - Viana, Rayana Pinheiro (2013)
The yacon is a tuberous root poorly consumed in Brazil lately been much studied on human health due to the presence of fructo-oligosaccharides (FOS). In the present study was produced flour from the yacon pulp and evaluated the influence of its intake of women with type 2 diabetes, during a period of 60 days (T0: in the beginning of the study; T30: after 30 days; T60: after 60 days). The participants were divided in a control group (CG: n = 29) and yacon group (YG: n = 23) who consumed 11 g of FOS present in yacon flour. The parameters evaluated were fasting glucose, lipid profile, body composition and the evaluation of food intake, adopting a 5% level of significance in statistical tests Yacon flour presented 6.50% of yield, 1.15% of moisture, 4.52% of total protein, 0.33 % of fat, 2.94% of ash, 10.23% of crude fiber, 91.0% of total carbohydrate and 35.06 % of FOS. In YG was observed a significant increase of HDL for the three study period (p < 0.0001), but there was also an increase of total cholesterol of T0 to T60 (p = 0.03) and significant reduction in percentage of body fat for T0 to T60 (p = 0.03). In the CG a significant increase was found for the HDL from T0 and T30 to T60 (p < 0.0001) parameters and triglycerides from T0 to T30 (p = 0.01). In the relation to the food intake, there was a significant difference between the groups in relation to the fiber in T30 and T60 (p = 0.01/p = 0.009). YG presented a significant reduction of calories (p = 0.02) and saturated fatty acids (p = 0.02) of T0 to T60 and CG a significant reduction of carbohydrate intake of T0 to T30 (p = 0.03). The decrease in the percentage of body fat and energy intake of the GY suggests a possible beneficial effect of FOS